Shutter Island - Lehane, Dennis (William Morrow, an imprint of HarperCollins Publishers, 2021)
U.S. Marshal Teddy Daniels and his partner, Chuck Aule, come to Shutter Island's Ashcliffe Hospital in search of an escaped mental patient, but uncover true wickedness as Ashcliffe's mysterious patient treatments propel them to the brink of insanity.